2007
DOI: 10.1111/j.1096-3642.2007.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic analysis of the genus Eunice (Eunicidae, polychaete, Annelida)

Abstract: Species of Eunice are distributed worldwide, inhabiting soft and hard marine bottoms. Some of these species play significant roles in coral reef communities and others are commercially important. Eunice is the largest and most poorly defined genus in Eunicidae. It has traditionally been subdivided in taxonomically informal groups based on the colour and dentition of subacicular hooks, and branchial distribution. The monophyly of Eunice and of its informal subgroups is tested here using cladistic analyses of 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…The family Eunicidae Berthold, 1827 is a very speciose family with nine genera and with more than 400 valid species distributed worldwide (Zanol and Read 2012). The genus Marphysa comprises around 81 nominal species with five valid species only known from European waters (Read and Bellan 2016): Marphysa bellii (Audouin & Milne Edwards, 1833), Marphysa fallax Marion & Bobretzky, 1875, Marphysa kinbergi McIntosh, 1910, Marphysa sanguinea and Marphysa totospinata Lu & Fauchald, 1998.…”
Section: Introductionmentioning
confidence: 99%
“…The family Eunicidae Berthold, 1827 is a very speciose family with nine genera and with more than 400 valid species distributed worldwide (Zanol and Read 2012). The genus Marphysa comprises around 81 nominal species with five valid species only known from European waters (Read and Bellan 2016): Marphysa bellii (Audouin & Milne Edwards, 1833), Marphysa fallax Marion & Bobretzky, 1875, Marphysa kinbergi McIntosh, 1910, Marphysa sanguinea and Marphysa totospinata Lu & Fauchald, 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Eunicida represents one of the higher, morphologically most well-described clades of polychaetes (Struck et al 2006, Zanol et al 2007a), but, being an order containing 7 recognised families (Eunicidae is one of them) and > 900 nominal species in 100 genera (Rouse & Pleijel 2006) some uncertainties still persist. Focusing on the taxonomy, phylogeny and ecology of species in the genus Lysidice, data on molecular phylogeny have only recently indicated that this genus is paraphyletic with respect to Marphysa and Nicidion, while Nematonereis is nested within the Lysidice (Zanol et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…However, diagnostic features of many Leodice species have been well studied under the names of Eunice species by the previous works (Hartman 1944, Day 1967, Miura 1977, 1986, Fauchald 1992, Carrera-Parra and Salazar-Vallejo 1998, Zanol et al 2000, Steiner et al 2002, Zanol et al 2007, Wu et al 2013b). The new species of the present study can be discriminated from its relatives by the distinguishing morphological features provided by these previous works.…”
Section: Systematic Accountsmentioning
confidence: 99%
“…Among the species assigned to this group, L. duplexa sp. n. is closely related to L. antennata , the type specie of Leodice , in the following morphological features: the antennae and palps are regularly articulated and moniliform; the compound falcigers are bidentate; the peristomial and notopodial cirri are articulated; the branchiae are pectinate and show the bimodal distribution of branchial filaments; the aciculae are yellow (Hartman 1944, Day 1967, Imajima 1967, Miura 1977, 1986, Fauchald 1970, 1992, Zanol et al 2007, Wu et al 2013b). Nonetheless, the new species is distinguishable from L. antennata in two points as follows: the new species has 2–4 aciculae, while L. antennata bears one pair; the subacicular hooks are paired in some chaetigers in the new species, but always single in each chaetiger in L. antennata (Day 1967, Imajima 1967, Miura 1977, Fauchald 1992, Zanol et al 2007, Wu et al 2013b).…”
Section: Systematic Accountsmentioning
confidence: 99%
See 1 more Smart Citation